THE IMPORTANCE OF USING MANAGERIAL STRATEGIES BY THE TOURISTIC FIRMS FROM ALBA COUNTY - CORDOȘ, Mălina (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
In the current economic context, characterized by a dynamic, unstable and uncertain environment, by competition’s regional, national and global exacerbation, designing tourism strategies – probably, and obviously possibly, one of the key factors in the Romanian economic social development – is a difficult, but absolutely necessary step, regardless of size, ownership or territorial profile of the companies acting in this field. Big changes are expected to happen in the Romanian tourism during the coming years. In our opinion, they will be more important than those that occurred in the last and a half decade. The opportunities arising in the market will increase by the emergence of new consumers, a new social and economic environment, new products and services, new destinations, new information and distribution channels. Both large and small tour operators can and will take advantage of these benefits and opportunities. Thus, many questions arise: What kind of strategies and what kind of investments or products will be required in the future? What tourist destinations will be the most attractive? If we were to make a bet on the future, what will be the impact of information and communication technologies on tourism? How can we stimulate innovation in tourism? What initiatives and what strategies will need to be emphasized?